The H-induced fracture behavior in hot rolled medium Mn steels with and without δ-ferrite. (November 2022) - Wang, Zheng; Wan, Zhongmin; Chen, Xi; Xu, Juanping; Zhou, Yao; Huang, Taiming; Kong, Xiangzhong; Ou, Changjie; Zhang, Jing; Li, Jinxu
Highlights: The fracture behavior on RD//TD and RD//ND plane is consistent when the microstructure is homogeneous γ and α. Thin plate morphology δ-ferrite results in the extremely different fracture behavior on RD//TD and RD//ND plane. δ-ferrite is a state of plane stress on RD//TD surface, while the layered δ-ferrite and γ + α is more like a composite material on RD//ND plane. The distance of dislocation walls in TEM is approximately equaled to the width of rugged quasi-cleavage river pattern strips on fractograph of δ-ferrite. Abstract: The objective of this research is to investigate the H-induced fracture behavior of Fe-6Mn-0.2C-3Al-0/0.6Si steels. Two hot-rolled steels are inter-critical annealed (0Si and 0.6Si), containing γ + α-ferrite. Additionally, 0.6Si contains abundant δ-ferrite, exhibiting thin plate morphology. As for 0Si, H-induced cracks (HICs) nucleate at γ(α')/α interfaces. Then HIC's propagation is not only transgranular cracking but also intergranular cracking. However, H-induced fracture behaviors of 0.6Si on various planes are different. As for RD//TD surface, HICs preferentially nucleate at boundaries and interior of δ-ferrite, thus reveal the intergranular cracking and the transgranular cracking, contributing to the rugged river pattern strips on fractograph. As for RD//ND surface, the layered coarse-grained δ-ferrite and layered fine-grained γ + α-ferrite are stacked in sequence, which is like a composite material. The existence of the shear stress and dislocation pile-up at interfaces of (γ(α') + α)/δ and γ(α')/α results in HIC's preferential nucleation. Then, HICs preferentially pass through the structure of γ(α') + α-ferrite.